(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify the level of practicing administrative financial , educational and legal authorities granted to the general directorates in Baghdad and all governorates except Kurdistan region from the point of view of the general directors and their assistance . The study included the entire research community due to the limited number of the sample reached (60) individuals. The researcher approved the questionnaire as a research tool prepared by him. Depending on the mentioned authorities and powers, he used the weighted mean, the seminal weight, standard deviation, and Prison correlation to analyze his research data. the results showed a weakness of many general directorates of education in implementing the power granted to them by law due to their weak staff ,lack of experience on one hand , and the higher authorities stick to these power on other hand , or weak ownership of the required resources and tools . The study concluded with many recommendations, the most important are: 1 – The importance of knowledge and conviction by all actors of the principle and mechanism of delegating power. 2 – That the delegation of powers requires the presence of educational leaders with a high degree of willingness and self – confidence and ability to undertake required tasks.